The Contextual Meanings of Preposition ‘by’ Found in an English Textbook - Nur Alfika; Ahmad Talib; Chairil Anwar Korompot (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The objectives of this research are (1) to find out the number of contextual meanings of preposition ‘by’ found an English textbook, (2) to find out the most dominant contextual meanings of preposition ‘by’ found in an English textbook. This research employed qualitative with descriptive qualitative method. The subject of this research was the English textbook entitle Introducing Translation Studies by Jeremy Munday. The instrument in collecting data were the documentation of the list of contextual meaning of preposition ‘by’ found in an English textbook. Based on the research finding and discussion, there were at least 16 contextual meanings of the preposition 'by' which must be used in context. From the data it can be seen that the most frequently used constant meaning is the meaning of ‘by’ which there are at least 48 sentences in the book that use the preposition 'by' in it. Keywords: Contextual meaning, preposition ‘by’, Translation Studies